Kajian Pengembangan Lahan Pertanian Tanaman Pangan Berbasis Komoditas Unggulan di Kabupaten Pinrang, Sulawesi Selatan - Suryani Suryani; Santun R. P. Sitorus; Untung Sudadi (Jurnal Wilayah dan Lingkungan, 2020)
Agriculture sector performs prominent role in the economy of Pinrang Regency. As the national food-estate area of South Sulawesi Province, RGDP agriculture sector of the regency increased from 4.72 to 7.94 trillion IDR in 2013-2017. This study aims to analyze food-crop agriculture land development based on primary commodities in Pinrang Regency, South Sulawesi. This study was conducted in twelve sub-districts in the regency’s area from September 2018 to June 2019. Application of geospatial technology was expected to present new approach with more accurate and easily updated land development planning in the area. The research data consisted of primary field survey data and secondary data of spatial pattern map of RTRW 2012-2032 from Bappeda and food-crop harvested area and production from BPS Pinrang Regency, characteristics and existing land use map from BBPPSDLP, and forest and water conservation area map from KLHK. Primary commodities was detemined based on Location Quotient and Shift Share Analysis. Potential land arrangement was referred to FAO Land Suitability Evaluation. Land development plan was formulated using selection and screening procedure based on Boolean logic. Five primary commodities was determined with 5,871 Ha potential land suitable for their development out of 7,324 Ha available land that consisted of land uses planned for paddy (3,529 Ha), cassava (1,398 Ha), corn (657 Ha), soybean (187 Ha), and sweet potato (100 Ha). The land development plan for these commodities was categorized into the first (147 Ha) and second (5,724 Ha) priority.